1998
DOI: 10.1093/rheumatology/37.5.502
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate reduces inflammatory cell numbers, expression of monokines and of adhesion molecules in synovial tissue of patients with rheumatoid arthritis

Abstract: Methotrexate (MTX) is one of the most widely prescribed drugs in the treatment of rheumatoid arthritis (RA). The mechanism by which MTX exerts its anti-rheumatic effect has not yet been defined. The aim of the present study was to investigate the effect of MTX treatment (7.5-15 mg/week) on synovial tissue in RA. For this purpose, synovial biopsies were taken from 11 RA patients before and 16 weeks after initiation of MTX therapy. Immunohistochemistry was performed using monoclonal antibodies (MAb) specific for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 2 publications
9
85
0
Order By: Relevance
“…The specific effect of leflunomide and methotrexate on the number of macrophages and T cells in synovial tissue samples was more pronounced at 4 months, and there was also a marked effect of both compounds on the expression of adhesion molecules, a finding consistent with previous observations after methotrexate treatment (43). These changes were even more noticeable in the patients who fulfilled the ACR 20% response criteria.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The specific effect of leflunomide and methotrexate on the number of macrophages and T cells in synovial tissue samples was more pronounced at 4 months, and there was also a marked effect of both compounds on the expression of adhesion molecules, a finding consistent with previous observations after methotrexate treatment (43). These changes were even more noticeable in the patients who fulfilled the ACR 20% response criteria.…”
Section: Discussionsupporting
confidence: 88%
“…This appears to be especially beneficial for the evaluation of novel specific therapies such as TNF␣ blockade (40,41), and anti-CD4 monoclonal antibodies (32). For treatment with conventional DMARDs and biologics with diverse effects (42), the changes might be more diffuse and do not necessarily represent a specific effect (43)(44)(45)(46). In this study, we observed, in general, a similar response after 4 months of treatment with either leflunomide or methotrexate.…”
Section: Discussionsupporting
confidence: 52%
“…However, the current study is limited in its capacity to evaluate the complete implication of DCs in the pathogenesis of RA: the small number of patients, variability in patient's factors at study entry (disease duration, previous DMARD treatment [46,47]). It has to be continued in order to allow statistical correlations and to prove the importance of adhesion and co-stimulatory molecules expression on DCs as targets for future immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite renal clearance of MTX, the reduction in renal function associated with CSA use did not result in serious MTX toxicity. CSA also inhibits T cell function and interleukin-2 production (33), and MTX acts on macrophages (34). CSA has been demonstrated to delay radiologic damage (35)(36)(37) and is effective in both early (38) and established RA, as well as in combination with MTX in partial responders to MTX (13,14).…”
Section: Discussionmentioning
confidence: 99%